2022
DOI: 10.5093/psed2021a11
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Communication Style as Predictor of Cyberbullying, Emotional Wellbeing, and Personal Moral Beliefs in Adolescence

Abstract: Peer-to-peer violence has been increasing globally amongst youth, both inside and outside of school (UNICEF, 2017). Cyberbullying refers to a particular form of violence among peers, which is often considered an extension of bullying, defined as willful and repeated harm imposed through electronic means (Patchin & Hinduja, 2006). Thus, it can occur anywhere through social media. Cyberbullying may affect adolescents' mental health and well-being and, in turn, relate to difficulties in school adjustment and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…El estudio de (13), examinó la autoestima familiar y escolar en adolescentes involucrados en conductas agresivas, encontrando niveles más bajos de autoestima en agresores y en aquellos que eran tanto agresores como víctimas, mientras que las víctimas y los no implicados mostraron niveles más altos. Esto sugiere una posible relación entre la autoestima y la participación en conductas agresivas.…”
Section: Abstract: Aggression; Well-being; Students; Relationship; Un...unclassified
“…El estudio de (13), examinó la autoestima familiar y escolar en adolescentes involucrados en conductas agresivas, encontrando niveles más bajos de autoestima en agresores y en aquellos que eran tanto agresores como víctimas, mientras que las víctimas y los no implicados mostraron niveles más altos. Esto sugiere una posible relación entre la autoestima y la participación en conductas agresivas.…”
Section: Abstract: Aggression; Well-being; Students; Relationship; Un...unclassified
“…The literature has previously examined aggressive communication in interpersonal contexts. For instance, Pereira et al (2022) found that using an aggressive communication style predicted cyberbullying perpetration and lower emotional well-being and moral beliefs among adolescent peer relationships. In addition, Kennedy-Lightsey and Myers (2009) found that young adults who use aggressive communication are more likely to use antisocial behaviors in peer conflicts.…”
Section: Literature Reviewmentioning
confidence: 99%